Development of Shredding Machine for Plastic Recycling - Suliman, Muhammad Syahmi; Johar, Muhammad Akmal (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Abstract sentence introduce the rersearch background. The second sentence explains the main research objectives, aims and scopes of study. The third sentences describes the materials and methods used to conduct the study. the fourth sentences presents the results and discussion of the study. the fifth sentences describes the conclusion of the study.